A concepção socialista de universidade na etapa inicial da Revolução Cubana - Mario Mariano Ruiz Cardoso (2022)
This text brings the results of the research focused on understanding the socialist concept of university that was consolidated in the Cuban Revolution in the 1960s. The theoretical and methodological framework of the research is Marx's Social Theory, as well as the expression of his rich tradition, with special emphasis on Latin American Marxism. The analyzed data are documental and bibliographical, and part of them were collected on a visit to Cuba in February 2019. In order to clarify the political and pedagogical content of the investigated conception, the text presents the following items: 1) an introduction indicating the general dimensions of the research; 2) the Marx thought on knowledge and emancipation; 3) the roots of the conception studied here, with emphasis on the 1918 Cordoba Reform, the José Carlos Mariátegui ideas about education, university and socialism and the Julio Antonio Mella thought and political life regarding the relationship between university and socialism in Cuba in the 1920s; 4) Student struggles in Cuba before 1959 and their relationship with the Cuban working class mobilizations against the Fulgencio Batista regime; 5) The context of educational transformations after 1959 and the 1962 University Reform in Cuba already in the heart of the victory of the Cuban Revolution; 6) Ernesto Che Guevara's thoughts on university and socialism; 7) Fidel Castro's ideas on education and university in the socialist transition in Cuba in the 1960s. The set of results obtained point to the consolidation of a socialist conception of university in the 1960s in the Cuban Revolution, which must be understood in its relationship with the totality of the revolutionary process underway in that period. This conception pointed to the incorporation of the working masses to the set of social achievements, among them higher education, the centrality of revolutionary Marxist theory and its tradition for university education, the importance of the student movement's leading role in the university's new directions, the articulation between technical-scientific education and revolutionary education, the focus on socialization, knowledge production and formation of professionals to meet the needs of the revolution and the socialist transition initiated.